Social Security : The Story of British Social Progress and the Beveridge Plan - Great Britain. Inter-departmental Committee on Social Insurance and Allied Services; Davison, Ronald C. (Ronald Conway), 1884- (London : G.G. Harrap and Co., 1943)
1943 1943 1940s 3 preliminary leaves, 9-62 pages : illustrations, diagrams Requirements of a single man [Picture] of a single woman [Picture] of a married couple [Picture] Each circle represents 1 shilling per week at 1938 prices 26 15X/2/566/303